Inhibition of epithelial CC-family chemokine synthesis by the synthetic chalcone DMPF-1 via disruption of NF-κB nuclear translocation and suppression of experimental asthma in mice - Rajajendram, Revathee; Tham, Chau Ling; Akhtar, Mohamad Nadeem; Sulaiman, Mohd Roslan; Israf Ali, Daud Ahmad (Hindawi Publishing Corporation, 2015)
Asthma is associated with increased pulmonary inflammation and airway hyperresponsiveness. The interaction between airway epithelium and inflammatory mediators plays a key role in the pathogenesis of asthma. In vitro studies evaluated the inhibitory effects of 3-(2,5-dimethoxyphenyl)-1-(5-methylfuran-2-yl)prop-2-en-1-one (DMPF-1), a synthetic chalcone analogue, upon inflammation in the A549 lung epithelial cell line. DMPF-1 selectively inhibited TNF-α-stimulated CC chemokine secretion (RANTES, eotaxin-1, and MCP-1) without any effect upon CXC chemokine (GRO-α and IL-8) secretion. Western blot analysis further demonstrated that the inhibitory activity resulted from disruption of p65NF-κB nuclear translocation without any effects on the mitogen-activated protein kinase (MAPK) pathway. Treatment of ovalbumin-sensitized and ovalbumin-challenged BALB/c mice with DMPF-1 (0.2–100 mg/kg) demonstrated significant reduction in the secretion and gene expression of CC chemokines (RANTES, eotaxin-1, and MCP-1) and Th2 cytokines (IL-4, IL-5, and IL-13). Furthermore, DMPF-1 treatment inhibited eosinophilia, goblet cell hyperplasia, peripheral blood total IgE, and airway hyperresponsiveness in ovalbumin-sensitized and ovalbumin-challenged mice. In conclusion, these findings demonstrate the potential of DMPF-1, a nonsteroidal compound, as an antiasthmatic agent for further pharmacological evaluation.